An Efficient Design of the Piezoresistive Pressure Sensor Applied for Micro Aerial Vehicle - Pham, Anh-Duc; Nguyen, Trieu Khoa; Le, Hong Hieu; Dang, Phuoc Vinh (International Journal of Integrated Engineering, 2023)
In this research, the developing process of a piezoresistive pressure sensor working in the atmosphere environment applied in micro aerial vehicle using the MEMS fabrication method is introduced. The sensor consists of four Au/Cr piezoresistors in a Wheatstone bridge configuration on a wet oxidized silicon diaphragm. To fabricate the sensor, three lithographic steps were conducted: the first one is to define the resistors and Au/Cr lines/pads, the second and the third ones are to determine the width and the thickness of the square SiO2/Si diaphragm, respectively. The sensor diaphragm shape and thickness were defined by the anisotropic etching of Si in tetramethylammonium hydroxide (TMAH) solution, and the resistors array are formed by sputtering and wet etching method. The sensor size is ~6000 Âµm by 6000 Âµm. The sensor output voltage was measured for various applied pressure levels from 0 to 1.2 bar with 5V voltage supply. The fabricated sensor also exhibits a sensitivity of 50.01 mV/bar.